UTILIZING CRITICAL DISCOURSE ANALYSIS FOR DEVELOPING STUDENTS' DIGITAL LITERACY: A NEED ANALYSIS APPROACH - Oktarin, Irene Brainnita; Hastomo, Tommy (Universitas Indo Global Mandiri, 2023)
The research aimed to analyze the need for implementing Critical Discourse Analysis to improve students' digital literacy skills. The research focuses on analyzing the problems and needs of students majoring in Management at STIE Gentiaras Lampung regarding the need to apply Critical Discourse Analysis to improve students' digital literacy skills. Qualitative descriptive is a type of research used by researchers. Meanwhile, STIE Gentiaras Lampung students were the subjects used in this study. There are literature studies, observations, interviews, and tests as data collection methods in the study. There are four analyses of problems experienced by students in order to develop students' digital literacy skills. The four problems are 1) Low Digital Literacy Skills of Students, 2) Mismatch of Teaching Methods in The Classroom, 3) Lack of Integration in the Curriculum, and 4) Lack of Access and Infrastructure. Needs analysis is also carried out by researchers, in addition to applying problem analysis. STIE Gentiaras Lampung students have three needs. First, students need CDA as a learning method to develop their digital literacy skills. Second, students need CDA integration with the latest curriculum. Third, students need adequate access and infrastructure to develop digital literacy skills. Therefore, researchers will continue this research by using CDA as a learning method to develop students' digital literacy skills. Keywords : CDA, digital literacy, need analysis